Potentiometric Studies of Bivalent Metal Ions with Adenine and Nitrilotriacetic Acid - Verma Shalini; Dharmveer Singh; Krishna V. (International Journal of Research in Chemistry and Environment (IJRCE), 2016)
A potentiometric titration technique has been used to determine the stability constants of the various bivalent metal ions, Co(II), Ni(II), Cu(II), Zn(II), Cd(II), and Pb(II) with biologically important nucleobases (Adenine) and aminopolycarboxylic acid (Nitrilotriacetic acid ) at 30±1 °C and ionic strength I = 0.1 M (NaNO3). The acid-base properties of both ligands were investigated and discussed. The protonation constants of ligands Adenine (A) and Nitrilotriacetic acid (B) were determined and used for determination of stability constants of the ternary (1:1:1) and quaternary (1:1:1:1) systems in aqueous solution. The observed concentration of species formation of ternary and quaternary complexes of metal complexes obtained by SCOGS computer program and represented in graphical form using ORIGIN 6.1. The species formation curves of various ternary and quaternary complexes reveal that the complex formation was found to occur in simultaneously manner. The Stability constants of ternary and quaternary complexes were calculated by SCOGS computer program using potentiometric pH-metric titration values. The order of stability constant of quaternary system has been discussed and found that the complex species MA, MB, MAB and M1M2AB type followed the Irving William order of stability constants. The species formation curves of each metal complexes occurring at different physiological pH has been shown in figures and discussed briefly.